2015
DOI: 10.1101/cshperspect.a023408
|View full text |Cite
|
Sign up to set email alerts
|

Confrontation, Consolidation, and Recognition: The Oocyte’s Perspective on the Incoming Sperm

Abstract: From the oocyte's perspective, the incoming sperm poses a significant challenge. Despite (usually) arising from a male of the same species, the sperm is a "foreign" body that may carry with it additional, undesirable factors such as transposable elements (mainly retroposons) into the egg. These factors can arise either during spermatogenesis or while the sperm is moving through the epididymis or the female genital tract. Furthermore, in addition to the paternal genome, the sperm also carries its own complex re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 135 publications
(189 reference statements)
0
11
0
Order By: Relevance
“…Whether sperm RNAs are necessary for early embryonic development remains controversial 129131 , particularly given the recent generation of parthenogenetic mice with appreciable survival rates 132,133 ; nonetheless, their potential synergistic action with maternal RNAs have been discussed with interest 134 . Thus far, the most significant biological functions identified for sperm RNAs are their involvement in non-Mendelian inheritance in mammals, such as the paramutation phenomenon in mice (BOX 2), and their contribution to the intergenerational inheritance of paternally acquired traits, including mental and nutritional stresses 9,2426 .…”
Section: Figurementioning
confidence: 99%
“…Whether sperm RNAs are necessary for early embryonic development remains controversial 129131 , particularly given the recent generation of parthenogenetic mice with appreciable survival rates 132,133 ; nonetheless, their potential synergistic action with maternal RNAs have been discussed with interest 134 . Thus far, the most significant biological functions identified for sperm RNAs are their involvement in non-Mendelian inheritance in mammals, such as the paramutation phenomenon in mice (BOX 2), and their contribution to the intergenerational inheritance of paternally acquired traits, including mental and nutritional stresses 9,2426 .…”
Section: Figurementioning
confidence: 99%
“…Mature sperm cells contain complex 'populations' of different RNA subtypes, known to be important for fertilization and early embryo development [82]. Interestingly, it has been suggested that small non-coding RNAs, piRNA and micro-RNA, may play important roles in the verification of the cytoplasmic and genetic compatibility of gametes prior to fertilization [83]. In this process, non-coding sperm RNAs may recognize their respective binding sites in oocyte RNAs.…”
Section: (D) Rna and Extracellular Vesiclesmentioning
confidence: 99%
“…5 Nevertheless, the presence of such a diverse RNA profile takes on added significance in view of their potential to be delivered to the oocyte, along with the paternal genome, whereupon they may contribute to fertilization and embryo development and fitness. 3,[9][10][11] This implies that, rather than simply being a legacy of the spermatogenic process, these transcripts may actually have fitness consequences and potentially adaptive value. 12 As an extension of this hypothesis, it has recently been proposed that sperm RNA could encode information about the paternal environment, with males having the capacity to modify the RNA content of their sperm under different conditions to prime the embryo to develop appropriately within the prevailing environment.…”
Section: Introductionmentioning
confidence: 99%